Improvement of 800-m running performance with prior high-intensity exercise - Ingham, S. A.; Fudge, B. W.; Pringle, J. S.; Jones, A. M. (International Journal of Sports Physiology and Performance, 2013)
Prior high-intensity exercise increases the oxidative energy contribution to subsequent exercise and may enhance exercise tolerance. The potential impact of a high-intensity warm-up on competitive performance, however, has not been investigated. Purpose: To test the hypothesis that a high-intensity warm-up would speed VO2 kinetics and enhance 800-m running performance in well-trained athletes. Methods: Eleven highly trained middle-distance runners completed two 800-m time trials on separate days on an indoor track, preceded by 2 different warm-up procedures. The 800-m time trials were preceded by a 10-min self-paced jog and standardized mobility drills, followed by either 6 × 50-m strides (control [CON]) or 2 × 50-m strides and a continuous high-intensity 200-m run (HWU) at race pace. Blood [La] was measured before the time trials, and VO2 was measured breath by breath throughout exercise. Results: 800-m time-trial performance was significantly faster after HWU (124.5 ± 8.3 vs CON, 125.7 ± 8.7 s, P < .05). Blood [La] was greater after HWU (3.6 ± 1.9 vs CON, 1.7 ± 0.8 mM; P < .01). The mean response time for VO2 was not different between conditions (HWU, 27 ± 6 vs CON, 28 ± 7 s), but total O2 consumed (HWU, 119 ± 18 vs CON, 109 ± 28 ml/kg, P = .05) and peak VO2 attained (HWU, 4.21 ± 0.85 vs CON, 3.91 ± 0.63 L/min; P = .08) tended to be greater after HWU. Conclusions: These data indicate that a sustained high-intensity warm-up enhances 800-m time-trial performance in trained athletes.